Bukan Irregularitas Siklus Menstruasi, Namun Menorrhagia sebagai Faktor Risiko Keputihan Patologis Pada Siswi SMA Full Day di Surabaya - Tri, Yuniarti Rini; Budi, Amalia Rize; Atika, Atika; Cahyaning, Putri Eka Arum; Bambang, Purwanto (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Adolescence was the age most at risk for women to experience vaginal discharge. Symptoms accompanying pathological vaginal discharge were more frequently complained of by female full day high school students in Surabaya. Until now, the risk factors associated with symptoms of pathological vaginal discharge in full-day high school students in Surabaya were still unclear. To analyze menstrual history which has the potential to be a risk factor for symptoms of pathological vaginal discharge in full day female students in Surabaya. Female students of SMA Muhammadiyah 2 Surabaya grades 10 and 11 were chosen as the accessible population, because they follow the learning curriculum 5 days a week, from 06.00 to 16.00 WIB. Each respondent was asked to fill out a questionnaire containing questions about the history of vaginal discharge and menstruation experienced in the last three cycles using a cross-sectional approach. Data were analyzed statistically using contingency tables and the Chi Square test to prove the relationship between variables. All respondents had menarche, never had sex and experienced vaginal discharge. Seventy one percent of respondents complained symptoms of pathological vaginal discharge. Most of them were experience for prolonged menstrual day duration in regular menstrual cycle. Menorrhagia, but not irregular menstrual cycles were associated with pathological vaginal discharge symptoms. Female students with a history of prolonged menstrual duration were 2,327 times more likely to complain of symptoms of pathological vaginal discharge. It was not an irregular menstrual cycle, but menorrhagia as a risk factor associated with pathological vaginal discharge symptoms.  Keywords: Menorrhagia, Menstruation, Pathological Vaginal Discharge, Itching, Adolescent  ABSTRAK Remaja merupakan usia yang paling berisiko bagi perempuan mengalami keputihan. Gejala yang menyertai keputihan patologis lebih banyak dikeluhkan oleh siswi SMA full day di Surabaya. Sampai saat ini, faktor risiko yang berhubungan dengan gejala keputihan patologis pada siswi SMA  full day di Surabaya belum diketahui. Tujuan untuk menganalisis riwayat menstruasi yang berpotensi menjadi faktor risiko dari gejala keputihan patologis pada siswi full day di Surabaya. Siswi SMA Muhammadiyah 2 Surabaya kelas 10 dan 11 dipilih sebagai populasi terjangkau, karena mengikuti kurikulum belajar 5 hari seminggu, mulai pukul 06.00 sampai dengan pukul 16.00 WIB. Setiap responden diminta mengisi keuesioner yang berisi pertanyaan tentang riwayat keputihan dan menstruasi yang dialami dalam tiga siklus terakhir dengan pendekatan cross sectional. Data dianalisis secara statistik menggunakan tabel kontigensi dan  uji Chi Square untuk membuktikan hubungan antar variabel. Semua siswi yang menjadi responden telah menarche dan belum pernah berhubungan seks. Seluruh responden mengalami keputihan dan 71% responden mengeluhkan gejala keputihan patologis. Siklus menstruasi yang tidak teratur tidak berhubungan dengan gejala keputihan patologis. Siswi yang memiliki riwayat durasi hari menstruasi memanjang berisiko 2,327 kali mengeluhkan gejala keputihan patologis. Bukan siklus menstruasi yang iregular, namun menorrhagia sebagai faktor risiko yang berhubungan dengan gejala keputihan patologis. Kata Kunci: Menorrhagia, Menstruasi, Keputihan Patologis, Gatal, Remaja